The Features of Vegetables in Indonesia and The Current Policy in The Framework of Agricultural Development - Mohamad Maulana; Bambang Sayaka (Analisis Kebijakan Pertanian, 2007)
Vegetables are grown throughoutIndonesia, especially on high altitude areas. Indonesians traditionally consume vegetables for their daily food. The objectives of this paper are (1) to describe status and characteristics of agriculture and vegetables inIndonesiaand (2) to illustrate current policy in the framework of agricultural development. The results showed that during the period of 1998 – 2005 the trend of vegetable tended to decline in harvested area and stagnant in production. On the other hand, vegetable consumption inIndonesiais very small. Budget allocation for vegetable increased from 8.96 percent of total food expenditure in 1996 to 9.91 percent in 2002. During the same period, vegetable import value fluctuated. However, the share of vegetable export value showed a constant performance, especially during 1999 – 2003 period, namely 0.09 – 0.11 percent. Entering global market, increasing strategies currently implemented in developing horticulture products are aimed at increasing production, yields, and improving quality through efficient farm management to produce competitive products.